The Roles of Technology in the Classroom According To Teacher, Student and School Administrator: Who Wants Technology in the Classroom and Why? - Özden Şahin İzmirli; Erhat Köse (Anı Publishing, 2018)
In the research conducted in the 2017-2018 spring term in a private high school in İstanbul, the roles for technology in the classroom according to teacher, student and administrator were examined. The research was carried out in a two-stage design with the use of mixed design. Teachers, students and school administrators have tried to determine the roles they have assigned technologically through the quantitatively, then qualitatively. The quantitative data of the study were collected from 104 students, 25 teachers and four school administrators. Qualitative data of the study were collected from nine students, seven teachers and one school administrator. It can be suggested that the roles of the stakeholders given to technology in the research are in line with each other. It is seen that stakeholders give roles for educational purpose and student benefit.